Acute and chronic effects of plyometric exercise performed with hypoxia on post-activation performance enhancement (PAPE) - Betul Coskun; Michael J. Hamlin (PLoS ONE, 2025)
In the literature, no study is available either to investigate the effects of conditioning activity (CA) applied in hypoxic conditions on post-activation performance enhancement (PAPE) or to examine whether hypoxic long-term training can affect PAPE. This study aims to test the effects of plyometric exercise applied under hypoxia on PAPE, which is the acute effect; and to test the same effect again after an 8-week plyometric training, which is a potential chronic effect on the acute performance improvement after an adaptation with training. Nineteen team-sports athletes received 8-week drop-jump (DJ) training in Low-Normobaric Hypoxia (Low-NH, n = 8), Normobaric-Normoxia (NN, n = 6), or High-Normobaric Hypoxia (High-NH, n = 5) conditions (SpO 2 of 90%, 97–100%, and 80%, respectively) two times per week. PAPE was tested at the 2 nd and 4 th minutes of recovery after normoxic and hypoxic CA with 1x5 DJs at the pre-test, and tested after an 8-week training period following a normoxic and hypoxic CA with 1x8 DJs at the post-test. As a result of repeated measures ANOVA to identify the acute effects, only under normoxic conditions, DJ-height was significantly higher in the 2 nd (31.7 ± 4.9 cm) and 4 th minute (31.6 ± 4.3 cm) than baseline (30.1 ± 4.7 cm) (p < 0.05). Regarding the chronic-effect results, only the High-NH group significantly increased DJ-height from baseline (31.6 ± 4.5 cm) to the 2 nd (33.7 ± 5.9 cm) and 4 th minutes (34.5 ± 4.6 cm) (p < 0.05), without testing condition (hypoxic/normoxic) separately, at the end of the 8-week training period. It is concluded that plyometrics with acute hypoxic CA have no beneficial effect on PAPE responses, but 8 weeks of plyometric training with normobaric hypoxia may lead to an adaptation to induce improved PAPE.